Ethical challenges in end-stage dementia: Perspectives of professionals and family care-givers - Hochwald, Inbal Halevi (Nursing ethics, 2021)
Background:In Israel, caring for people with end-stage dementia confined to home is mainly done by home care units, and in some cases by home hospice units, an alternative palliative-care service. Because life expectancy is relatively unknown, and the patient’s decision-making ability is poor, caring for this unique population raises ethical dilemmas regarding when to define the disease as having reached a terminal stage, as well as choosing between palliative and life-prolonging-oriented care.Objectives:Exploring and describing differences and similarities of professional staff members’ (PSMs’) and family caregivers’ perceptions of caring for people with end-stage dementia in two different settings.Design:Qualitative research, using semi-structured interviews analyzed through a thematic content–analysis approach.Participants:Sixty-four interviews were conducted (24 PSMs and 40 family caregivers) in two care-settings—home hospice unit and home care unit.Ethical considerations:The study was approved by the Ethics Committee (BBL00118-17).Findings:We found dilemmas regarding palliative care to be the main theme, including definition of the disease as terminal, choosing “comfort” over “life-prolonging,” clarifying patients’ wishes and deciding whether or not to use artificial feeding.Discussion:Both PSMs and family caregivers deal with ethical dilemmas and have reached different conclusions, both legitimate. Comprehending dementia as a terminal disease influenced participants’ perceptions of the relevancy of palliative care for people with end-stage dementia. Discrepancies between PSMs and family caregivers in caring for people with end-stage dementia were found in both home hospice unit and home care unit environments, raising potential conflicts regarding decisions for end-of-life care.Conclusions:Communication between PSMs and family caregivers is crucial for the discussion about the discrepancies regarding the unique dilemmas of caring for people with end-stage dementia and bridging the gap between them. Lack of communication and resources can hamper the provision of an acceptable solution for quality and equality of care in the best interest of people with end-stage dementia.